Meningkatkan Minat Belajar Siswa Dengan Metode PjBL dengan Bantuan Media Audio Visual pada Kelas X Fase E di SMK Negeri 2 Sibolga Tahun Pelajaran 2023/2024 - Peradi Misa M. Bangun (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This research aims to determine the improvement of the Project Based Learning learning model on the learning outcomes of class This research was conducted at SMK Negeri 2 Sibolga. With a total of 15 students. Classroom action research is a scientific activity carried out by teachers in the classroom using actions to improve the quality of learning. Apart from that, classroom action research also aims to improve a teacher's professionalism. So, classroom action research is very important for teachers to carry out, because solving existing educational problems will help improve the quality of education in Indonesia. Therefore, researchers will discuss how important it is to carry out classroom action research.